Deporte, investigación y patentes en España. - Herrero Pérez, Rosario (Revista General de Información y Documentación, 2000)
An overview of tbe Spanish patents related to sports technologies usted on the CIBEPAT database, with an analysis of tbeir total volume, tbematic dis tribution, types of requested patents and a more detailed study on the 1990-99 decade.